Reflective Practices in Arts Education - Burnard, Pamela; Hennessy, Sarah; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This book is focused on the role of reflective practice, as a source and resource for teaching and learning, and research in the arts. It aims to investigate the concept of reflection and its application to a range of contemporary arts education contexts for both teachers and learners. For beginning and experienced teachers the book offers practical ideas and frameworks for thinking critically about their own teaching (and learning) as well as providing insights into work taking place in other arts disciplines. The growing field of arts partnerships and artist/educators is also well represented by case studies and descriptions of specific practical strategies.
Perspectives on Reflection -- Rethinking the Imperatives for Reflective Practices in Arts Education -- Adolescents and Cultures of Reflection -- Cultural Reflections -- Reflective Creativity -- Teaching Arts as Reflective Practice -- Challenges for Artists and Teachers Working in Partnership -- Tools of Reflection -- Game for Reflection -- Reflection and Evaluation -- Using Learner Journals in Teacher Education in the Arts -- Reflective Use of Digital Technologies in the Arts -- Tools for Developing Reflective Skills -- Case Studies: Reflections in and on Action -- Reengagement through Peer Teaching Drama -- Cross-and Intercultural Engagement -- Reflective Practice through the Lens of a Fifth Grade Composition-based Music Class -- Fair Exchange -- The Conditions and Consequences of Reflective Practices in Arts Education.
Keywords: EDUCATION; EDUCATION; ART & MUSIC EDUCATION